If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 = 9 + -4u Solving 1 = 9 + -4u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '4u' to each side of the equation. 1 + 4u = 9 + -4u + 4u Combine like terms: -4u + 4u = 0 1 + 4u = 9 + 0 1 + 4u = 9 Add '-1' to each side of the equation. 1 + -1 + 4u = 9 + -1 Combine like terms: 1 + -1 = 0 0 + 4u = 9 + -1 4u = 9 + -1 Combine like terms: 9 + -1 = 8 4u = 8 Divide each side by '4'. u = 2 Simplifying u = 2
| 3x-(2x+1)=9 | | 11+3p=-6p-7 | | y=-10x^2-40x | | (-29)-17= | | (x^2+3x-2)(x+3)= | | -16x^2+24x+2=0 | | 5y-2=-14-3y | | 18x-12= | | -7(z+5)=-8z | | k-17=(-12) | | -41=6x+7(x-17) | | 5+4x-16=9 | | -w+9=-31 | | 2.5x=5x-3-x | | a+3=12-10 | | 7x+5(x-12)=12 | | f(x)=-6x^5+9x^4-12x^3-15 | | (19x-7)+(6x-12)= | | 3(x+4)=4(3+21) | | -4=0.5p-7 | | 6y+2-y=6+4y-10 | | 3x+7x-30=12+50+20x | | h(x)=16x^2+65x+5 | | ln(11X-3)=0 | | 2x+5=6x+8 | | 35-37=8 | | 3.8n-13=1.4n+15 | | b-12=-16 | | -9x+24=80-2 | | 12a-4b-15a+b= | | 7+2[n-5]n=3.6 | | 9ac+6a= |